IMPLIKASI PENERAPAN ONE STOP SERVICE PELAYANAN PERIZINAN TERPADU TERHADAP MENINGKATNYA IKLIM INVESTASI DI KABUPATEN KUDUS - Nor Khalimah; Puji Astuti; Supratiwi . (Journal of Politic and Government Studies, 2013)
The purpose of this study was to determine the extent of one stop service has been implemented by KPPT Kudus Regency will directly impact on the high business license so as to increase the chances of the investment climate. Indicators of successful implementation of OSS using Standar Pelayanan Minimal (SPM) in accordance with Decree No. 63 of 2003 MENPAN analyzed descriptively by looking at the phenomenon that is happening in the community. Looking at the various aspects that have been analyzed can be concluded that the ease of licensing after the implementation of OSS that can boost a business license so investment opportunities in the Kudus Regency is getting better.Keywords: OSS, Licensing and Investment.